The change in optical characteristics of ZnO crystals under ruby laser irradiation - Markevich, I.V.; Kushnirenko, V.I.; Baidullaeva, A.; Bulakh, B.M.; Pobirovskiy, P.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The influence of pulsed ruby laser irradiation on luminescence and optical transmission spectra of nominally undoped ZnO single crystals was investigated. Both treatment and measurements were performed at 300 K. The irradiation was found to cause the increase of crystal transmission in absorption edge region and the rise of shortwave wing of exciton luminescence with respect to its longwave one. These changes were accompanied with the rise of electric conductivity. The analysis of obtained results in common with earlier data led to the conclusion that the movement of mobile shallow donors from dislocations to crystal bulk took place under the influence of ultrasound wave excited by laser pulse. The decrease of shallow donor density near dislocations resulted in the shrinkage of c-band state density “tail” in these regions, which caused the shift of the optical absorption edge to the shortwave side.